A State of Biopreparedness. Issue Volume 34:Issue s1(2019) (May 2019) - Varshney, Kavita; Friend, Caren; Bag, Shopna; Murphy, Margaret; Dempsey, Kathy; Clark, Penelope; Ferguson, Patricia
Abstract : Introduction: Westmead Hospital (WMH) recognized gaps in its preparedness to respond to the Ebola 2014 outbreak in West Africa. A fragmented system was identified. A 'State of Bio-preparedness' project team convened to discuss all healthcare services in the planning, training, and implementation of a biopreparedness response. Methods: A survey targeting the staff's competence and confidence in biologically hazardous infection management was conducted. Semi-structured interviews explored staff members' experiences and perspectives of biopreparedness response. The collaborative team called "State of Biopreparedness" (SOB) was assembled and a clinical practice improvement project was undertaken. To assess readiness, nine simulated Viral Haemorrhagic Fever (VHF) exercises involving staff and consumers were conducted. These exercises were debriefed by the multidisciplinary committee and themes and issues were identified. These nine simulation drills then assessed readiness and evaluated performance. Results: A number of consistent issues continue to emerge including: 1. A standard communication pathway for notification was needed - use of the incident paging system (111 pages) to notify the hospital's incident management team. 2. A consistent and coordinated approach to the training and maintenance of standardized and high-level Personal Protective Equipment (PPE) protocols for frontline clinical and clinical staff was required. 3. Clear delineation of roles and responsibilities and supporting these roles by translating the VHF Control Guideline and policy into task cards and checklists. 4. Strengthening intra- and interdepartmental staff collaboration and communication. 5. Infection control measures to be taken by staff after identifying a patient with possible VHF to reduce the risk of transmission of disease to staff, other patients, and visitors. Discussion: Integrating disaster management processes with clinical protocols had a positive impact on the hospital's biopreparedness response. Simulation exercises were a vital and practical way for staff to feel confident and competent to perform their roles.